2008
DOI: 10.1007/s10900-008-9131-7
|View full text |Cite
|
Sign up to set email alerts
|

Who Wants to Quit? Characteristics of American Indian Youth Who Seek Smoking Cessation Intervention

Abstract: No group is more at-risk for tobacco-related health disparities than are American Indian youth. Little is known about their readiness to quit smoking and the extent to which cessation programs may require cultural tailoring related to recruitment, implementation, or content. This study identifies unique characteristics of American Indian teen smokers who enrolled in a school-based smoking cessation program, Not On Tobacco (called N-O-T). Using data from N-O-T intervention trials conducted in North Carolina bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Both studies reported non-significant changes in abstinence rates between intervention and control groups at follow-up, but both also indicated that community and participant interest and need warranted further study. Other studies document the tobacco smoking prevalence 15 , the importance of culturally relevant programs 16,17 , and special challenges in AI populations and their efforts to abstain from tobacco 18 . The authors are aware of no published studies that use culturally tailored text messaging to support tobacco cessation in AI populations.…”
mentioning
confidence: 99%
“…Both studies reported non-significant changes in abstinence rates between intervention and control groups at follow-up, but both also indicated that community and participant interest and need warranted further study. Other studies document the tobacco smoking prevalence 15 , the importance of culturally relevant programs 16,17 , and special challenges in AI populations and their efforts to abstain from tobacco 18 . The authors are aware of no published studies that use culturally tailored text messaging to support tobacco cessation in AI populations.…”
mentioning
confidence: 99%